Recent changes in human resources for health and health facilities at the district level in Indonesia: evidence from 3 districts in Java - Harahap Nida P; Heywood Peter; Aryani Siska (BMC, 2011)
Abstract Background There is continuing discussion in Indonesia about the need for improved information on human resources for health at the district level where programs are actually delivered. This is particularly the case after a central government decision to offer doctors, nurses and midwives on contract the chance to convert to permanent civil service status. Our objective here is to report changes between 2006 and 2008 in numbers and employment status of health staff in three districts following the central government decision. Methods Information was derived from records at the district health office and, where necessary for clarification, discussions with district officials. Results Across the three districts and all public sector provider categories there was an increase of almost 680 providers between 2006 and 2008 - more than 300 nurses, more than 300 midwives and 25 doctors. The increases for permanent public servants were proportionately much greater (43%) than the total (16%). The increase in those who are permanent civil servants was greatest for nurses (51%) and midwives (35%) with corresponding decreases in the proportion of staff on contract. There was considerable variation between the three districts. Conclusions There has been a significant increase in the number of healthcare providers in the 3 districts surveyed and the proportion now permanent public servants has increased even more than the increase in total numbers. The changes have the effect of increasing the proportion of total public expenditure allocated to salaries and reducing the flexibility of the districts in managing their own budgets. Because public servants are allowed private practice outside office hours there has also been an increase in the number of private practice facilities offering health care. These changes illustrate the need for a much improved human resources information system and a coherent policy to guide actions on human resources for health at the national, provincial and district levels.